Readings in multimedia computing and networking - Jeffay, Kevin; Zhang, HongJiang, 1960- (San Francisco : Morgan Kaufmann Publishers, 2002)
Readings in Multimedia Computing and Networking captures the broad areas of research and developments in this burgeoning field, distills the key findings, and makes them accessible to professionals, researchers, and students alike. For the first time, the most influential and innovative papers on these topics are presented in a cohesive form, giving shape to the diverse area of multimedia computing. The seminal moments are recorded by a dozen visionaries in the field and each contributing editor provides a context for their area of research by way of a thoughtful, focused chapter introduction. The volume editors, Kevin Jeffay and HongJiang Zhang, offer further incisive interpretations of past and present developments in this area, including those within media and content processing, operating systems, and networking support for multimedia. This book will provide you with a sound understanding of the theoretical and practical issues at work in the field's continuing evolution. * Offers an in-depth look at the technical challenges in multimedia and provides real and potential solutions that promise to expand the role of multimedia in business, entertainment, and education. * Examines in Part One issues at the heart of multimedia processes: the means by which multimedia data are coded, compressed, indexed, retrieved, and otherwise manipulated. * Examines in Part Two the accommodation of these processes by storage systems, operating systems, network protocols, and applications. * Written by leading researchers, the introductions give shape to a field that is continually defining itself and place the key research findings in context to those who need to understand the state-of-the art developments.
Part I: Multimedia Processing and Retrieval -- Chapter 1 -- Digital Audio -- edited by HongJiang Zhang and Hao Jiang -- Chapter 2 -- Digital Image and Video Compression and Processing -- edited by Bing Zeng -- Chapter 3 -- Audio Retrieval and Navigation Interfaces -- edited by Philippe Aigrain -- Chapter 4 -- Content-Based Image Indexing and retrieval -- edited by HongJiang Zhang -- Chapter 5 -- Content-Based Video Browsing and Retrieval -- edited by HongJiang Zhang -- Part II: Systems, Networking and Tools -- Chapter 6 -- Multimedia Database Systems -- edited by Aidong Zhang -- Chapter 7 -- Multimedia Operating systems -- edited by Klara Nahrstedt -- Chapter 8 -- Videoconferencing -- edited by Kevin Jeffay -- Chapter 9 -- Networking and Media Streaming -- edited by Ketan Mayer-Patel -- Chapter 10 -- Multimedia storage Servers -- edited by Prashant J. Shenoy and Harrick M. Vin -- Chapter 11 -- Multimedia Synchronization -- edited by Lawrence A. Rowe -- Chapter 12 -- Authoring Systems -- edited by Dick C.A. Bulterman.
Includes bibliographical references and index.
Keywords: Multimedia systems; Computer network; Electronic books